Diversidade genética e análise de tendência entre acessos tradicionais de feijoeiro comum (Phaseolus vulgaris L.) por meio de marcadores moleculares e morfológicos - Guidoti, David Teixeira (2011)
The germplasm banks are conservative units of the genetic material of a specie for an immediate or future use. The genetic diversity characterization is important for the correct use of these genetic resources mainly by the improvement programs. Concerning about the common bean (Phaseolus vulgaris L.), which stands out as one of the most cultivated leguminous in the world there are international and national germplasm banks and, among these, there is one belonging to the Universidade Estadual de Maringá, the Common Bean Germoplasm Bank (CBGM) of Núcleo de Pesquisa Aplicada à Agricultura (Nupagri) in which are kept around 181 accessions of the specie. Therefore, according to the exposed above, the present research had as objective to analyze by molecular markers and morphoagronomic traits the genetic diversity found among 17 common bean accessions from CBGM. The genetic diversity was obtained with basis on the combined analysis of all the evaluated characteristics, using the Genetics Platform SAS - Statistical Analysis System. A dissimilarity matrix was elaborated with basis on the Jaccard coefficient, which was used to construct a dendogram, validated by Multidimensional Scaling Analysis and Non-Orthogonal Principal Components. Moreover, it was carried out the Cochran-ArmitageTendency Analysis, with the aim to test the markers quantitatively, associating them to the agronomic and morphological characteristics observed. According to the genetic diversity analysis it was possible to cluster the accessions into two large groups, one composed by eleven accessions from Andean gene pool while the other six from Mesoamerican gene pool. The highest genetic dissimilarity was obtained between the BGF 13 accession and the group CL04 (BGF 1, BGF 4, BGF 5, BGF 12 and BGF 18). The most similar accessions were BGF 2 x BGF 3, BGF 6 x BGF 11 and BGF 9 x BGF 17. The Cochran-Armitage Trend Test was efficient on the identification of loci microsatellites with the trend-binding to morphoagronomic traits, such as, BMd-9 and BMd-42 to the gene pool, BMd- 10, BMd-12 and BMd-46 to the growing habit and BMd-42 with relation of the reaction to the 2047 race of C. lindemuthianum. Therefore, according to the results obtained, it was possible to conclude that the analysis were efficient in detecting the genetic diversity existent among the accessions analyzed, such as loci microsatellites with the trend-binding to rpho-agronomic traits thus enabling the insertion of this germplasm in common bean improvement programs.